2013
DOI: 10.1136/amiajnl-2013-001625
|View full text |Cite
|
Sign up to set email alerts
|

Combining rules and machine learning for extraction of temporal expressions and events from clinical narratives

Abstract: The system provides a state-of-the-art method that can be used to support automated identification of mentions of clinical events and temporal expressions in narratives either to support the manual review process or as a part of a large-scale processing of electronic health databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…Traditionally, the sodium polystyrene sulfonate trigger is used to identify cases in which excessive potassium is administered, yet the poor PPV (27%) of sodium polystyrene sulfonate may in part be due to its recommended and appropriate use in TLS. 21 Hyperkalemia is a potentially life-threatening consequence of TLS, and frequent potassium measurements and oral administration of sodium polystyrene sulfonate are recommended. 21 Additionally, multiple nephrotoxic agents are often used in the treatment of oncology patients, and even careful monitoring may not prevent renal impairment with resultant hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the sodium polystyrene sulfonate trigger is used to identify cases in which excessive potassium is administered, yet the poor PPV (27%) of sodium polystyrene sulfonate may in part be due to its recommended and appropriate use in TLS. 21 Hyperkalemia is a potentially life-threatening consequence of TLS, and frequent potassium measurements and oral administration of sodium polystyrene sulfonate are recommended. 21 Additionally, multiple nephrotoxic agents are often used in the treatment of oncology patients, and even careful monitoring may not prevent renal impairment with resultant hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…21 Hyperkalemia is a potentially life-threatening consequence of TLS, and frequent potassium measurements and oral administration of sodium polystyrene sulfonate are recommended. 21 Additionally, multiple nephrotoxic agents are often used in the treatment of oncology patients, and even careful monitoring may not prevent renal impairment with resultant hyperkalemia. Vitamin K was not ordered for patients on warfarin experiencing an ADE but instead was prescribed for patients experiencing chemotherapy or disease-induced thrombocytopenia, veno-occlusive disease, or malabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in a similar clinical NER challenge in 2012 [24] showed that using supplementary training data (in addition to the one provided by the organizers) could have a positive effect on the performance of the ML models. Based on that, we experimented with enriching the training data with the data set provided in the 2014 de-identification challenge.…”
Section: Methodsmentioning
confidence: 88%
“…Other top approaches used adapted regular expressions (Sohn et al, 2013) on top of the off the shelf Heideltime system (a general-domain NLP system for parsing time expressions) (Strötgen and Gertz, 2010). Another approach used a hybrid system where the output from a CRF-based system was combined with the output of a rule-based system (Kovačević et al, 2013).…”
Section: Introductionmentioning
confidence: 99%